A sceptical approach to 'the everyday': Relating Stanley Cavell and Human Geography. Issue 79 (February 2017) - Pugh, Jonathan
Abstract: Over the past few decades there has been a turn toward 'the everyday' in the social sciences and humanities. For some authors, this turn is about making the everyday a new repository of authority of some sort, political, social, cultural or otherwise. For others, however, any turn toward the everyday interrupts any such evaluation. Focusing upon Stanley Cavell and the philosophical lineage that he continues from Emerson, Nietzsche, Thoreau and Wittgenstein, this paper examines Cavell's interest in the menace and power of scepticism as key to understanding the everyday as a lived experience. As an introduction to this particular part of Cavell's work for many Geographers, the paper puts Cavell in relation to more familiar approaches to the everyday, including de Certeau, critical Human Geography, non-representational theory, affect theory, psychoanalysis and pragmatism.